Prevention of pressure ulcers, malnutrition, poor oral health and falls in nursing homes: A focus group study with nurse aides, registered nurses and managers - Merita Neziraj; Magdalena Andersson; Peter Hellman; Malin Axelsson; Christine Kumlien (Elsevier, 2021)
Background: Despite available knowledge how to prevent the risk of pressure ulcers, malnutrition, poor oral health and falls among older persons in nursing homes, these risks still frequently occur and cause a major burden for older persons; furthermore, for the health care system, they are extremely costly. One way to combat these risks is to register the prevention process in quality registries. However, the increasing older population worldwide is going to put high demands on those working with this group of people.Objective: To explore how nurse aides, registered nurses and managers in nursing homes experience working with the prevention of pressure ulcers, malnutrition, poor oral health and falls in general and according to the quality register Senior Alert care process.Methods: A qualitative study was conducted in nursing homes in a municipality in southern Sweden. We purposively sampled nurse aides, registered nurses and managers (n = 21) working in nursing homes registered in the quality register Senior Alert, who then participated in one of five focus group semistructured digital interviews held between February and April 2020. The interviews were audio recorded. Data were analysed using reflexive thematic analysis.Results: Our findings explore how nurse aides, registered nurses and managers experience working with the prevention of pressure ulcers, malnutrition, poor oral health and falls in nursing homes both in general and according to Senior Alert. The following four themes were generated during the analysis: (1) is included in the everyday work, (2) requires team effort, (3) requires handling many challenges and (4) requires finding strategies.Conclusion: The prevention of pressure ulcers, malnutrition, poor oral health and falls among older persons in nursing homes is complex. There is a commitment and responsibility among nurse aides, registered nurses and managers regarding preventive work and team effort, and finding useful strategies is necessary for the work to be successful. However, challenges, both at the individual and organizational levels, are involved, which implies that smoother organizational routines facilitating this preventive work are needed. Although nurse aides, registered nurses and managers are good at finding strategies that facilitate this work, one of the main challenges seems to lie in the variety of knowledge found among those working in nursing homes, particularly among nurse aides. This challenge was voiced by all the professionals, which suggests the need for a tailored educational intervention aimed at increasing the related knowledge among those working in nursing homes to enhance preventive work.